Sosialisasi Peningkatan Efisiensi dan Efektivitas Produk Recycle Coconut Shell Melalui Pemberdayaan Masyarakat Dalam Persfektif Islam di Desa Kuala Lagan Kabupeten Tajung Jabung Timur - Isnaeni, Nurida; Enggrani Fitri, Lucky; Dean Amri, Ary; Roihan, Muhammad; Pratiwi, Heni (PT. Alahyan Publisher Sukabumi, 2024)
The main objective of carrying out this service is to increase public understanding of the potential and value of recycled coconut shell products, encourage active community participation in coconut shell management and integrate Islamic values ​​in sustainable natural resource management practices. The implementation method used is through outreach and training to the community regarding the use of coconut shells as raw material for recycling coconut shells, an Islamic perspective approach to protecting nature and resources, providing technical support in the production process, and monitoring and evaluating program progress. The results obtained can increase the number of recycled coconut shell products produced by the community, and increase community participation and the application of Islamic values ​​in natural resource management practices.